Preliminary results from the removal of Phosphorus compounds with selected sorption material - Kasprzyk, Magda; Wojciechowska, Ewa; Obarska–Pempkowiak, Hanna; Thomas, Marta (International Conference “Environmental Engineering”, 2017)
Due to the fact that resources of phosphorous are limited and are expected to get exhausted in the next 30 years the management of this resource has become extremely important. Most of the phosphorus compounds are lost forever, because they are discharged with sewage into surface water, causing eutrophication and in this way generating further issue and challenge. The aim of the study was to investigate the capacity to retain phosphorus compounds on sorption material. During the experiments, both synthetic and real wastewater were used. The synthetic wastewater simulated the composition of the reject water (RW) generated during the mechanical dewatering of the digested sewage sludge, and the real RW comes from WWTP in Gdansk. The investigation in steady conditions was carried out with Phoslock® which is chemically lanthanum clay. The results of the investigation are related to the determination of the sorption capacity with respect to the analyzed content of phosphorus compounds for stable conditions the determination of hydraulic load and way and time of mixing. For the synthetic wastewater the removal efficiency of phosphorous was 99.8% while for reject water (RW) generated during the mechanical dewatering of the digested sewage sludge was lower and equal to 85%.